Polymerization kettle for high-viscosity PETG or PCTG, and polymerization method for PETG or PCTG

By designing a horizontal polymerization kettle containing low viscosity zones, medium and high viscosity zones, and using a detachable single-piece disc and a combined progressive scraper set, the high viscosity of PETG or PCTG melt during polymerization is solved. The low polymerization efficiency and difficulty in cleaning are achieved, polymerization products with high viscosity and excellent hue performance are extended, and the operation cycle of the device is extended.

CN118491450BActive Publication Date: 2025-02-11JIANGSU GUOWANG HIGH TECH FIBER CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410166671.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-06
Publication Date
2025-02-11
Estimated Expiration
2044-02-06

AI Technical Summary

Technical Problem

In the synthesis of PETG or PCTG, the rod climbing effect is caused by the large melt dynamic viscosity, the melt thickness on the polymerization kettle wall and disk reactor is too large, the mass transfer rate of the material becomes slow, the polymerization reaction efficiency is reduced, and the polymerization reaction efficiency is also sticky. The attached melt is difficult to clean, which shortens the operating cycle of the polymerization device.

Method used

A horizontal polymerization kettle is designed, including low-viscosity zones, medium- and high-viscosity zones, and adopts a detachable single-piece disc and a combined progressive scraper set to ensure the film-forming structure of the high-viscosity zone and the effective work of the scraper set. , improve polymerization efficiency and cleaning convenience.

Benefits of technology

Through the design of this polymerization kettle, the viscosity of PETG or PCTG melt can be significantly improved, the hue performance of the polymerization product can be improved, the operation cycle of the polymerization device can be extended, and it is easy to clean.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118491450B_ABST
    Figure CN118491450B_ABST
Patent Text Reader

Abstract

The present invention relates to a polymerization kettle for high-viscosity PETG or PCTG, and a polymerization method for PETG or PCTG. The polymerization kettle is provided with a front and rear double shaft, and a plurality of disc reactors are arranged on the double shafts, which are divided into a low-viscosity zone, a medium-high-viscosity zone, and a high-viscosity zone; the disc reactor in the high-viscosity zone is a single disc that can be quickly disassembled; a plurality of scrapers are also arranged on the wall of the polymerization kettle between each two adjacent single discs in the high-viscosity zone, and the distance between each scraper and the adjacent single disc is different, which can gradually reduce the thickness of the high-viscosity melt on the disc, reduce the load of the stirring motor, improve the efficiency of the polymerization reaction devolatilization, extend the operation cycle of the polymerization device, and facilitate the cleaning of the inner wall of the reactor. For the PETG / PCTG polymerization method, a self-developed germanium system or titanium-germanium composite catalyst is adopted, and the aforementioned polymerization kettle is adopted as the final polymerization kettle. The polymerization kettle of the present invention can prepare PETG or PCTG with high viscosity and excellent hue.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymerization kettle for high-viscosity PETG or PCTG and a polymerization method for PETG or PCTG. Background Art

[0002] PETG and PCTG are both transparent, non-crystalline copolyesters. Both can be prepared by esterification and polymerization of terephthalic acid PTA, ethylene glycol EG, and 1,4-cyclohexanedimethanol CHDM in the presence of an esterification catalyst and a polymerization catalyst. The two can be distinguished according to the different molar proportions of the segments corresponding to CHDM in the total diol (CHDM and EG) segments in the copolyester. Generally, the polymerization product with a molar proportion of 31% to 32% of the segments corresponding to CHDM is called PETG copolyester; and the polymerization product with a molar proportion of 60% to 62% of the segments corresponding to CHDM is called PCTG. Both polymerization products have high transparency, good toughness and impact strength, excellent low-temperature toughness, high tear resistance, good processing performance, and excellent chemical resistance. Both can be processed by traditional extrusion, injection molding, blow molding, and blister molding. Both can be widely used in the market of plates and sheets, high-performance shrink films, bottles, and profiles; they can also be used to produce toys, household utensils, and medical supplies.

[0003] When synthesizing PETG or PCTG in the prior art, an ordinary horizontal polymerization kettle is usually used, and an ordinary disc reactor is inside the polymerization kettle. When the two are polymerized, due to the high dynamic viscosity of the melt, the melt will have a climbing effect on the disc reactor, resulting in the accumulation of the melt on the disc reactor disc. The thickness of the melt on the polymerization kettle wall and the disc reactor is too large, and the material mass transfer rate slows down, which is not conducive to the further progress of the polymerization. In addition, the adhered melt will cause the load of the stirring motor of the disc reactor to increase, further reducing the polymerization reaction efficiency. At the same time, there are also great obstacles to cleaning the melt on the polymerization kettle and the disc reactor, which significantly shortens the operation cycle of the polymerization device.

[0004] And for PETG or PCTG melt, in the polymer macromolecular chain, PETG contains 31% to 32% CHDM structural units, PCTG contains 60% to 62% CHDM units, the rigid chain segment is combined with the cis-trans structure, and the steric hindrance is greatly increased. Therefore, the vibration and movement slip of the regional chain segments and chain segments of the polymer macromolecular chain are severely restricted when heated. Therefore, as the molecular weight of the polymer increases, the difficulty of macromolecular chain movement increases rapidly, which is manifested in the rapid increase of melt viscosity performance in the macroscopic view. It is very easy to coil under high viscosity state, and because the melt elasticity is poor, it is easy to produce shear thinning under high temperature state (278 to 285°C), and the film is very easy to break, making the polymerization reaction difficult to control. In addition, due to the slow mass transfer rate of the polymer material, the final melt viscosity is not large enough, and the color of the polymer product PETG or PCTG is not excellent enough. Summary of the invention

[0005] The invention aims to provide a high-viscosity PETG or PCTG polymerization kettle, which is used for preparing a high-viscosity PETG or PCTG melt. The high-viscosity PETG or PCTG melt prepared by the polymerization kettle has high viscosity, can significantly improve the hue performance of the polymerization product while ensuring other excellent properties, and the polymerization kettle can prolong the operation cycle of the polymerization device and is easy to clean.

[0006] Another object of the present invention is to provide a polymerization method of PETG or PCTG, which can prepare a PETG or PCTG polymerization product with high viscosity and significantly improved hue performance.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A polymerization kettle for preparing a PETG or PCTG melt, wherein the intrinsic viscosity of the PETG or PCTG melt is above 0.770, the polymerization kettle is a horizontal polymerization kettle, and comprises a main body containing a chamber inside, the main body comprises a low viscosity zone, a medium-high viscosity zone, and a high viscosity zone arranged in sequence along the axial direction of the polymerization kettle, and the viscosity of the PETG or PCTG melt in the low viscosity zone, the medium-high viscosity zone, and the high viscosity zone increases in sequence; the polymerization kettle also comprises two stirring shafts, one of which is arranged in the low viscosity zone, and the other is arranged in the high viscosity zone. The high viscosity zone and the medium-high viscosity zone; multiple disc reactors are arranged on the two stirring shafts, the disc reactor in the low viscosity zone is 6 to 8 groups of combined discs, each group is 3-10 discs; the disc reactor in the medium-high viscosity zone is 5 to 8 groups of double-disc or triple-disc combined discs; the disc reactor in the high viscosity zone is a single disc, and the single disc is detachably arranged in the polymerization kettle; a scraper group is also arranged on the wall of the polymerization kettle between each two adjacent single discs in the high viscosity zone, and the scraper group includes multiple scrapers, and the distance between each scraper and the adjacent single disc is different.

[0009] In the present invention, PETG refers to a copolyester of terephthalic acid PTA, ethylene glycol EG, and 1,4-cyclohexanedimethanol CHDM, and in the copolyester, the segment corresponding to CHDM accounts for 31% to 32% by mole in the total diol (CHDM and EG) segment; PCTG refers to a copolyester of terephthalic acid PTA, ethylene glycol EG, and 1,4-cyclohexanedimethanol CHDM, and in the copolyester, the segment corresponding to CHDM accounts for 60% to 62% by mole in the total diol (CHDM and EG) segment.

[0010] In the present invention, the distance between each scraper and the adjacent monolithic disk refers to the distance from the contact position between the scraper and the polymerization reactor wall to the adjacent disc reactor.

[0011] In the present invention, the combined disc refers to two or more adjacent disc reactors fixedly connected together to form a combined disc.

[0012] In some embodiments, the disc reactor in the high viscosity zone includes a ring and a plurality of spokes arranged inside the ring, the ring includes a first part and a second part, the first part is fixedly connected to the plurality of spokes respectively, and the second part is detachably connected to the first part.

[0013] In some embodiments, the detachable connection is a threaded connection.

[0014] The threaded connection method can be, for example, designing screw holes at the ends of the first part and the second part, and the two are matched, and then impact bolted together, so that the entire annular part forms a smooth overall disc, which can prevent dead corners from forming when the device is running.

[0015] In some embodiments, the plurality of spokes is 5 spokes.

[0016] In some embodiments, positioning screw holes are designed to extend left and right from the spoke top of the disc reactor in the high viscosity zone, and the rings of adjacent spokes are designed to be detachable segmented rings that cooperate with the screw holes at the spoke ends and are connected with impact bolts to form a smooth entire ring.

[0017] In some embodiments, the plurality of scrapers are arranged vertically, the ends of the scrapers point to the axis of the stirring shaft, and the projections of the plurality of scrapers on the plane where the disc reactor is located are located on the same circle.

[0018] In some embodiments, each scraper is the same length.

[0019] In some embodiments, the distance between the scraper and the adjacent previous single disk between each two adjacent single disks in the high viscosity area is distributed in an arithmetic progression. In combination with the projections of the plurality of scrapers on the plane where the disk reactor is located being located on the same circle, the scraper is actually installed in a spiral state between the two adjacent single disks.

[0020] In some embodiments, in each scraper set, the distance between the first scraper and the adjacent previous single-piece disk is 30-100 mm, and the distance between the last scraper and the adjacent next single-piece disk is 30-100 mm, preferably 40-80 mm, and more preferably 50-70 mm.

[0021] In some embodiments, in each scraper set, the axial distance between every two adjacent scrapers is 15 to 25 mm, preferably 20 to 25 mm. In the present invention, the axial distance between every two adjacent scrapers refers to the distance between the projections of the two adjacent scrapers on the stirring shaft.

[0022] In some embodiments, the scraper has a wedge-shaped cross section; the thick end of the wedge faces the rotation direction of the disc reactor.

[0023] In some embodiments, five scrapers are arranged between each two adjacent monolithic discs, and the number of scrapers is set to be the same as the number of spokes, so as to facilitate quick disassembly or cleaning.

[0024] In some embodiments, the total number of disc reactors in the low viscosity zone is 30 to 45, the total number of disc reactors in the medium-high viscosity zone and the high viscosity zone is 13 to 20, the total number of disc reactors in the high viscosity zone is 8 to 12, and 8 to 12 scraper groups are arranged in the high viscosity zone.

[0025] In some embodiments, the length of the low viscosity zone is half of the length of the polymerization kettle, the combined length of the medium-high viscosity zone and the high viscosity zone is half of the length of the polymerization kettle; and the length ratio of the medium-high viscosity zone to the high viscosity zone is 1:2.

[0026] In the present invention, one-half is not an exact mathematical value of one-half, but refers to a value approximately between one-half and about the same as one-half.

[0027] In some embodiments, the polymerization kettle further comprises a support base fixedly disposed on the inner wall of the main body for supporting two stirring shafts.

[0028] In some embodiments, the polymerization kettle further comprises a prepolymer inlet located at the bottom of the front end of the low viscosity zone and a high viscosity melt outlet located at the bottom of the rear end of the high viscosity zone, and the high viscosity melt outlet is in a bell-mouth shape.

[0029] In some embodiments, the diameters of the single disks in the high-viscosity zone decrease from front to back, and the diameter of the last single disk in the high-viscosity zone is 90% to 92% of the diameter of the first single disk.

[0030] In some embodiments, the distance between the disc reactor and the top of the polymerization vessel is 200-300 mm.

[0031] In some embodiments, the distance between the disc reactor and the bottom of the polymerization vessel is 20 to 50 mm.

[0032] The polymerization kettle of the present invention is provided with a single disk combination in the high viscosity zone to form a controllable film-forming structure in the high viscosity zone, and a combined progressive scraper group in the high viscosity zone is installed on the wall of the polymerization kettle. Preferably, each group of scrapers includes five scrapers (five sub-blades), and more preferably, the five sub-blades are spirally evenly distributed and installed between two adjacent single disks. Each group of scrapers starts from the first sub-blade from the front to the back (material advancement direction) and gradually decreases the distance between the scraper and the previous single disk along the inner circle of the polymerization kettle wall to the fifth sub-blade from the front to the back, thereby gradually reducing the thickness of the thickened high-viscosity melt film on the rotating ascending disk of the material, ensuring that the material surface on the disk is updated five times in each rotation cycle, and can complete two mixing effects at the lower two scraper sub-blades. Compared with the existing integrated hanging blade, the uniformly distributed split combined scraper has a more reasonable control over the film thickness of the high-viscosity melt, and the scraper load is greatly reduced. At the same time, the intermittent stress can form gravity sedimentation of the high-viscosity material in the middle of the disc, maintaining a good devolatilization channel in the middle space of the disc reactor, avoiding the current integrated scraper under high-viscosity conditions. The melt submerges the scraper and blocks the middle devolatilization channel. Therefore, the specific combined progressive scraper setting of the present invention can effectively improve the devolatilization efficiency of the high-viscosity area.

[0033] The present invention also provides a polymerization method for preparing PETG or PCTG by using the above-mentioned polymerization kettle for preparing PETG or PCTG melt, wherein the intrinsic viscosity of the PETG or PCTG is above 0.770, and the polymerization method comprises the steps of sequentially subjecting terephthalic acid, ethylene glycol and 1,4-cyclohexanedimethanol to esterification reaction in a first esterification kettle and a second esterification kettle, and subjecting the prepolymer to prepolymerization reaction in a first prepolymerization kettle and a second prepolymerization kettle to obtain a prepolymer, and subjecting the prepolymer to polymerization reaction in a final polymerization kettle to obtain the PETG or PCTG.

[0034] In some embodiments, the intrinsic viscosity of the PETG is 0.770-0.820, and the intrinsic viscosity of the PCTG is 0.790-0.820.

[0035] In some embodiments, the preparation method further comprises the step of adding an esterification catalyst to the first esterification kettle before the esterification reaction, wherein the esterification catalyst is selected from tetrabutyl titanate, tetraisopropyl titanate or tetra(2-ethylhexyloxy) titanate.

[0036] In some embodiments, the mass of the titanium element in the esterification catalyst accounts for 1 to 3 ppm of the mass of the PETG or PCTG.

[0037] In some embodiments, the esterification reaction in the first esterification kettle is carried out at a pressure of 70 to 80 kPa.

[0038] In some embodiments, the esterification reaction in the first esterification kettle is carried out at 255-257°C.

[0039] In some embodiments, the prepolymerization reaction in the first prepolymerization kettle is carried out under a vacuum degree of 9-12 kPa.

[0040] In some embodiments, the prepolymerization reaction in the first prepolymerization kettle is carried out under a vacuum degree of 9-12 kPa.

[0041] In some embodiments, the prepolymerization reaction in the first prepolymerization kettle is carried out at 258-266°C.

[0042] In some embodiments, the prepolymerization reaction in the second prepolymerization kettle is carried out under a vacuum degree of 0.9-1.3 kPa.

[0043] In some embodiments, the prepolymerization reaction in the second prepolymerization kettle is carried out at 260-267°C.

[0044] In some embodiments, the polymerization reaction in the final polymerization kettle is carried out under a vacuum degree of 100-130 Pa.

[0045] In some embodiments, the polymerization reaction in the final polymerization kettle is carried out at 265-275°C.

[0046] In some embodiments, the esterification reaction in the second esterification kettle is carried out under normal pressure.

[0047] In some embodiments, the second esterification kettle is a horizontal reactor and includes three chambers arranged in sequence from front to back. The preparation method further includes the step of injecting a polymerization catalyst into the third chamber from the front to the back of the second esterification kettle.

[0048] In some embodiments, the polymerization catalyst is selected from a germanium dioxide aqueous solution, a suspension of germanium dioxide dispersed in a mixed solvent of water and ethylene glycol, a surface-deposited supported germanium-based catalyst, and a surface-deposited supported titanium-germanium-based composite catalyst.

[0049] In some embodiments, the surface-deposited supported germanium-based catalyst and the surface-deposited supported titanium-germanium-based composite catalyst include a carrier, a supported deposition layer and an active component. The carrier is an inorganic porous material coated and modified by silicate. The supported deposition layer is located on the carrier and has a porous structure. The active component is deposited on the supported deposition layer.

[0050] In some embodiments, the surface deposited supported germanium-based catalyst is prepared by a preparation method comprising the following steps: subjecting a suspension of a carrier, a water-soluble calcium salt, a water-soluble aluminum salt, a water-soluble zirconium salt, a water-soluble hydroxide, and a base to a precipitation reaction, filtering, and calcining to form the supported deposited layer on the carrier; the base is selected from carbonates and / or bicarbonates; the specific surface area of ​​the carrier containing the supported deposited layer is greater than the specific surface area of ​​the carrier; the carrier containing the supported deposited layer is dispersed in water to obtain a suspension of the carrier containing the supported deposited layer; the suspension of the carrier containing the supported deposited layer is subjected to a hydrolysis reaction with a germanium source to obtain a catalyst precursor; the catalyst precursor is subjected to a coating reaction with a silicate and water to load an active component on the supported deposited layer to obtain a surface deposited supported germanium-based catalyst.

[0051] In some embodiments, the surface deposited supported titanium-germanium based catalyst is prepared by a preparation method comprising the following steps: subjecting a suspension of a carrier, a water-soluble calcium salt, a water-soluble aluminum salt, a water-soluble zirconium salt to a precipitation reaction with a water-soluble hydroxide and a base, filtering and calcining to form the supported deposition layer on the carrier; the base is selected from carbonates and / or bicarbonates; the specific surface area of ​​the carrier containing the supported deposition layer is greater than the specific surface area of ​​the carrier; the carrier containing the supported deposition layer is dispersed in water to obtain a suspension of the carrier containing the supported deposition layer; the suspension of the carrier containing the supported deposition layer is subjected to a hydrolysis reaction with a hydrochloric acid solution of a germanium source and a titanium source to obtain a catalyst precursor; the catalyst precursor is subjected to a coating reaction with a silicate and water to load an active component on the supported deposition layer to obtain a surface deposited supported titanium-germanium based composite catalyst.

[0052] In some embodiments, the inorganic porous material is selected from a combination of one or more of nanoporous alumina, nanoporous alumina-zirconia, nanoporous silica and nanoporous barium sulfate, and has a particle size of 20 to 80 nm, preferably 25 to 60 nm, more preferably 30 to 45 nm, and a specific surface area of ​​220 to 400 m 2 / g, preferably 230-320m 2 / g.

[0053] In some embodiments, the water-soluble calcium salt, water-soluble aluminum salt, and water-soluble zirconium salt used to prepare the carrier-loaded deposition layer are respectively selected from sulfates, acetates, or chlorides of the corresponding metal elements; and / or the water-soluble hydroxide is selected from one or both of sodium hydroxide and potassium hydroxide.

[0054] In some embodiments, the carbonate is selected from a combination of one or more of sodium carbonate, potassium carbonate and ammonium carbonate.

[0055] In some embodiments, the bicarbonate is selected from a combination of one or more of sodium bicarbonate, potassium bicarbonate and ammonium bicarbonate.

[0056] In some embodiments, the molar ratio of the water-soluble calcium salt, the water-soluble aluminum salt, and the water-soluble zirconium salt for preparing the carrier-loaded deposition layer is 0.5-2.5: 1.0-2.0: 0.8-3.5.

[0057] In some embodiments, the water-soluble calcium salt, water-soluble aluminum salt, and water-soluble zirconium salt are added dropwise to the suspension of the carrier in the form of aqueous solutions; the water-soluble hydroxide and alkali are added dropwise to the suspension of the carrier in the form of aqueous solutions; and the preparation method controls the simultaneous addition of the two.

[0058] In some embodiments, the molar concentration of the water-soluble calcium salt in the aqueous solution is 0.1 to 3.0 mol / L.

[0059] In some embodiments, the molar concentration of the water-soluble aluminum salt in the aqueous solution is 0.5 to 2.5 mol / L.

[0060] In some embodiments, the molar concentration of the water-soluble zirconium salt in the aqueous solution is 0.1 to 3.5 mol / L.

[0061] In some embodiments, the total molar concentration of the water-soluble hydroxide and the base in the aqueous solution is 0.1 to 2.0 mol / L.

[0062] In some embodiments, when forming the supported deposition layer on the support, the precipitation reaction is performed at a pH of 10-12.

[0063] In some embodiments, the precipitation reaction time is 8-11 hours.

[0064] In some embodiments, the precipitation reaction temperature is 70-100°C.

[0065] In some embodiments, the preparation method further includes the steps of continuing to stir the suspension for 1.0-4 hours after the precipitation reaction is completed, then pressurizing it to 0.7-1.2 MPa, stirring and heating it to 180-200°C, balancing it for 2-4 hours, then rapidly releasing the pressure to normal pressure, cooling the suspension to room temperature, filtering, washing, drying, and crushing.

[0066] In some embodiments, the preparation method further comprises a step of making pores in the carrier after the precipitation reaction and before filtration; preferably, the step of making pores in the carrier comprises the steps of pressurizing and heating the reaction system after the precipitation reaction and decompressing it to normal pressure.

[0067] In some embodiments, the pressurized pressure is 0.7-1.2 MPa.

[0068] In some embodiments, the heating is performed to a temperature of 180-200° C., which serves to decompose the carbonate hydroxide generated by the precipitation reaction, thereby increasing the specific surface area of ​​the carrier.

[0069] In some embodiments, when forming the supported deposition layer on the carrier, the temperature of the heat treatment is 290-310°C.

[0070] In some embodiments, the heating treatment time is 2-6 hours.

[0071] In some embodiments, the supported deposited layer is further dehydrated and made porous, and the specific surface area of ​​the supported powder containing the supported deposited layer after treatment is 600 to 900 m 2 / g, and the powder particle size is 20-50nm, and a large number of nanopores are formed on the powder surface.

[0072] In some embodiments, the germanium source is selected from one or both of germanium tetrachloride and tetraethylgermanium.

[0073] In some embodiments, the silicate is selected from a combination of one or more of tetraethyl silicate, tetrabutyl silicate, and tetrapropyl silicate.

[0074] In some embodiments, the germanium source is added dropwise to the suspension of the support containing the supported deposition layer to perform a hydrolysis reaction.

[0075] In some embodiments, the mass ratio of the silicate to the germanium source is 1:0.2-0.5.

[0076] In some embodiments, in the surface-deposited supported germanium-based catalyst, the mass ratio of the support, supported deposited layer, and effective germanium in the active component is 72.5-87.5:7.5-12.5:5.0-15.0. In the present invention, the effective germanium in the active component refers to the germanium element in the active component calculated by converting it into germanium dioxide in an equimolar manner.

[0077] In some embodiments, the preparation method further includes preparing a surface-deposited supported germanium-based catalyst in ethylene glycol under stirring conditions to form a suspension with a mass concentration of 10%-20%, stirring evenly, and then grinding and filtering to prepare a catalyst suspension. The catalyst suspension has an effective germanium element content (as germanium dioxide) of 1.0% to 3.0%, and is a stable suspension that can be stored for 3.0 to 5.0 months without sedimentation.

[0078] For germanium-based catalysts, in some embodiments, the preparation method further includes the steps of filtering, washing, and drying after loading the active components on the loaded deposition layer, and the loaded catalyst is in a powder state; preferably, the effective germanium content in the powdered loaded catalyst is 5.0% to 15.0%.

[0079] For titanium-germanium based catalysts, in some embodiments, the preparation method further includes the steps of filtering, washing, and drying after loading the active components on the loaded deposition layer, and the loaded catalyst is in a powder state; preferably, in the loaded catalyst in a powder state, the effective germanium content is 2.5% to 7.5%, and the effective titanium content is 0.6% to 1.9%.

[0080] In some embodiments, the germanium source is selected from one or both of germanium tetrachloride and tetraethylgermanium.

[0081] In some embodiments, the titanium source is selected from a combination of one or more of tetraisopropyl titanate, tetrabutyl titanate and titanium tetrachloride.

[0082] In some embodiments, the silicate is selected from a combination of one or more of tetraethyl silicate, tetrabutyl silicate, and tetrapropyl silicate.

[0083] In some embodiments, a hydrochloric acid solution of a germanium source and a titanium source are added dropwise to the suspension of the support containing the supported deposition layer to perform a hydrolysis reaction.

[0084] In some embodiments, the ratio of the mass of the silicate to the total mass of the germanium source and the titanium source is 1:0.2-0.5.

[0085] For titanium-germanium catalyst, in some embodiments, in the surface-deposited supported titanium-germanium-based catalyst, the mass ratio of the support, supported deposited layer, effective germanium in the active component, and effective titanium is 78.1-89.4: 7.5-12.5: 2.5-7.5 (in terms of germanium dioxide): 0.6-1.9 (in terms of titanium dioxide). In the present invention, effective titanium refers to the titanium element in the active component calculated by converting it into titanium dioxide in an equimolar manner.

[0086] In some embodiments, the molar ratio of titanium element to germanium element in the active component is 1:1.5 to 4.5.

[0087] For germanium-based catalysts, in some embodiments, the preparation method further includes the steps of filtering, washing, and adding a mixed solvent of water and ethylene glycol to disperse after loading the active component on the loaded deposition layer, and the loaded catalyst is in a suspension state.

[0088] For titanium-germanium based catalysts, in some embodiments, the preparation method further comprises the steps of filtering, washing, and adding a mixed solvent of water and ethylene glycol to disperse after loading the active components on the loaded deposition layer, and the loaded catalyst is in a suspension state.

[0089] In some embodiments, the particle size of the supported germanium-based catalyst and the titanium-germanium-based composite catalyst is 60-150 nm; and the specific surface area is 100-280 m 2 / g, the catalyst particle size is between nanometers and sub-nanometers, and the catalytic active centers on the catalyst particle surface can fully contact with the oligomers in a nanometer state, thereby improving the efficiency of the polymerization catalytic reaction.

[0090] When preparing the aforementioned surface-deposited nano-loaded germanium-based or titanium-germanium-based catalyst, firstly, a coprecipitation reaction of metal salts such as calcium, aluminum, and zirconium is carried out on the carrier to prepare a loaded deposition layer on the carrier, and the loaded deposition layer is a basic carbonate of three metals, and provides a loaded deposition site for the active component. The basic carbonate decomposes carbon dioxide gas after calcination, so that the loaded deposition layer has a porous structure, and the specific surface area of ​​the layer is greater than the specific surface area of ​​the carrier, that is, the present invention expands the specific surface area of ​​the carrier by precipitating a loaded deposition layer on the carrier, and at the same time, the carrier has more microporous structures, which is more conducive to the effective loading of the active component. Among them, the zirconium element in the loaded deposition layer can increase the strength of the carrier, and the calcium element and the aluminum element are conducive to forming the porous structure of the loaded deposition layer. When used to catalyze the synthesis of PETG or PCTG polyester, the in-situ deposited germanium element or the composite element of germanium element and titanium element has a larger specific surface area, and better catalytic activity and reaction efficiency can be obtained.

[0091] In some embodiments, the polymerization catalyst is selected from a germanium dioxide aqueous solution or a suspension of germanium dioxide dispersed in a mixed solvent of water and ethylene glycol, and the mass of germanium dioxide in the polymerization catalyst accounts for 100-150 ppm of the mass of PETG or PCTG.

[0092] In some embodiments, the polymerization catalyst is selected from a surface-deposited supported germanium-based catalyst, and the mass of the germanium element (in terms of germanium dioxide) in the polymerization catalyst accounts for 50 to 75 ppm of the mass of PETG or PCTG, preferably 40 to 90 ppm; more preferably 50 to 75 ppm.

[0093] In some embodiments, the polymerization catalyst is selected from the surface-deposited supported titanium-germanium based composite catalyst, and the mass of titanium element and germanium element (calculated as germanium dioxide) in the polymerization catalyst accounts for 8-12 ppm and 25-50 ppm of the mass of PETG or PCTG.

[0094] In some embodiments, the polymerization method further comprises the step of pre-melting 1,4-cyclohexanedimethanol and conveying the molten 1,4-cyclohexanedimethanol to the first esterification kettle.

[0095] In some embodiments, the polymerization kettle further includes steam feed ports for introducing superheated ethylene glycol steam, which are arranged at the top of the main body at the rear end of the low viscosity zone, the rear end of the medium and high viscosity zone, and the rear end of the high viscosity zone. The polymerization method further includes the step of using a metering system to meter the superheated ethylene glycol steam and introducing it into the final polymerization kettle.

[0096] In some embodiments, when preparing PETG, the feeding molar ratio of the terephthalic acid, ethylene glycol, and 1,4-cyclohexanedimethanol is 1: 0.92-0.93: 0.325-0.315; or, when preparing PCTG, the feeding ratio of the terephthalic acid, ethylene glycol, and 1,4-cyclohexanedimethanol is 1: 0.63-0.64: ​​0.610-0.615.

[0097] The present invention also provides PETG or PCTG prepared by the polymerization method of PETG or PCTG.

[0098] In some embodiments, the intrinsic viscosity of the PETG is 0.780-0.820 (phenol:tetrachloroethane 3:2).

[0099] In some embodiments, the PETG has a hue L value of ≧62.0 and a b value of ≦1.0, and has high chroma.

[0100] In some embodiments, the intrinsic viscosity of the PCTG is 0.800-0.820 (phenol:tetrachloroethane 3:2).

[0101] In some embodiments, the PCTG has a hue L value of ≧62.0 and a b value of ≦1.0, and has high chroma.

[0102] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0103] The polymerization kettle of the present invention is designed to quickly disassemble a single disk in the high viscosity area, and is equipped with a combined progressive scraper group, which can gradually reduce the thickness of the high viscosity melt on the disk, greatly reduce the load of the stirring motor, and improve the polymerization reaction efficiency. In particular, its detachable design greatly facilitates the manufacture of the reactor, overhaul of the device and cleaning of the inner wall of the reactor.

[0104] A detachable single disc is arranged in the high viscosity area of ​​the polymerization kettle, which cooperates with the combined progressive split scraper group, greatly reducing the difficulty of installing the internal parts of the final polymerization kettle. In addition, a gel carbonization layer is easily formed in the upper part of the polymerization kettle during the operation of the final polymerization kettle. When a conventional disc reactor is used for high-pressure cleaning of the reactor, it is difficult to clean due to the small space. The detachable single disc of the present invention can remove the detachable part, which greatly facilitates the construction operation.

[0105] By adopting the polymerization kettle of the present invention, PTEG or PCTG can be polymerized at a relatively low temperature (260-270° C.), and at the relatively low temperature, the PETG or PCTG melt has a higher dynamic viscosity, and the two high-viscosity melts can be uniformly attached to the disc reactor. At the same time, by designing a combined progressive scraper, the film-forming melt on the disc surface of the disc reactor can be cut to control the film thickness and improve the polymerization efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0106] Figure 1 It is a schematic structural diagram of the final polymerization kettle used in the embodiment;

[0107] Figure 2 It is a schematic diagram of a disc reactor in the high viscosity area of ​​the final polymerization reactor;

[0108] Figure 3 It is a schematic diagram of multiple disc reactors in the high viscosity area of ​​the final polymerization reactor;

[0109] Figure 4 It is a schematic diagram of the projection of the scraper in the high viscosity area of ​​the final polymerization kettle on the disc reactor;

[0110] Figure 5 This is a schematic diagram of the scraper structure in the high viscosity area of ​​the final polymerization kettle;

[0111] Figure 6 It is a three-dimensional schematic diagram of the scraper structure in the high viscosity area of ​​the final polymerization kettle;

[0112] Figure 7 It is another three-dimensional schematic diagram of the scraper structure in the high viscosity area of ​​the final polymerization kettle;

[0113] Among them, 1-low viscosity area, 2-medium and high viscosity area, 3-high viscosity area, 4-scraper, 5-ring, 6-first part, 7-second part, 8-spoke, 9-disc reactor, 10-stirring shaft, 11-support seat, 12-positioning screw hole. DETAILED DESCRIPTION

[0114] The above scheme is further described below in conjunction with specific examples; it should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions used in the examples can be further adjusted according to specific requirements, and the unspecified implementation conditions are usually the conditions in conventional experiments. Unless otherwise specified in the following examples, all raw materials are purchased from commercial sources or prepared by conventional methods in the art.

[0115] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0116] The present invention is further described below in conjunction with the accompanying drawings and preferred embodiments of the present invention. In the following embodiments, it should be noted that the terms "front" and "rear" are based on the flow direction of the material, the direction in which the material flows first is the front, and the direction in which the material flows later is the rear. Figure 1 In the term, the "front" refers to Figure 1 The term "back" refers to the right side of Figure 1 Therefore, the orientation and positional relationship described in the present invention are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, only have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention.

[0117] like Figure 1-7 As shown in the figure, the polymerization kettle for preparing PETG or PCTG melt of the present invention is a horizontal polymerization kettle, and includes a main body containing a chamber inside, the main body includes a low viscosity area 1, a medium-high viscosity area 2, and a high viscosity area 3 arranged in sequence along the axial direction of the polymerization kettle, and the viscosity of the PETG or PCTG melt in the low viscosity area 1, the medium-high viscosity area 2, and the high viscosity area 3 increases in sequence; the polymerization kettle also includes two stirring shafts 10, one of which is arranged in the low viscosity area 1, and the other stirring shaft 10 is arranged in the high viscosity area 3 and the medium-high viscosity area 2; the two stirring shafts A plurality of disc reactors 9 are arranged on the mixing shaft 10. The disc reactor 9 in the low viscosity zone 1 is composed of 6 to 8 groups of combined discs, each group of which is composed of 3 to 10 discs; the disc reactor 9 in the medium and high viscosity zone 2 is composed of 5 to 8 groups of double or triple combined discs; the disc reactor 9 in the high viscosity zone 3 is a single disc, and the single disc is detachably arranged in the polymerization kettle; a scraper group is also arranged on the wall of the polymerization kettle between each two adjacent single discs in the high viscosity zone 3, and the scraper group includes a plurality of scrapers 4, and the distance between each scraper 4 and the adjacent single disc is different.

[0118] The distance between each scraper 4 and the adjacent monolithic disk refers to the distance from the contact position of the scraper 4 with the polymerization reactor wall to the adjacent disk reactor 9 .

[0119] like Figure 2-5 As shown, the disc reactor 9 of the high viscosity area 3 includes a ring 5 and a plurality of spokes 8 arranged inside the ring 5, the ring 5 includes a first part 6 and a second part 7, the first part 6 is fixedly connected to the plurality of spokes 8, and the second part 7 is detachably connected to the first part 6. The detachable connection may be a threaded connection.

[0120] The threaded connection method can be, for example, to design screw holes at the ends of the first part 6 and the second part 7, and the two are matched and then impact bolted together, so that the entire ring 5 part forms a smooth overall disc, which can prevent dead corners from forming when the device is running.

[0121] like Figure 2-3 As shown, the spokes 8 of the disc reactor 9 in the high viscosity area are designed with positioning screw holes 12 extending to the left and right from the top, and the rings 5 ​​of the adjacent spokes 8 are designed with detachable segmented rings 5, which cooperate with the positioning screw holes 12 at the ends of the spokes 8 and are connected with impact bolts to form a smooth entire ring 5.

[0122] like Figure 6-7 As shown, the multiple scrapers 4 are arranged vertically, the ends of the scrapers 4 point to the axis of the stirring shaft 10, and the projections of the multiple scrapers 4 on the plane where the disc reactor 9 is located are located on the same circle.

[0123] Each scraper 4 has the same length. Between each two adjacent monolithic discs in the high viscosity area 3, the distance between the scraper 4 and the adjacent previous monolithic disc is distributed in an arithmetic progression. In view of the projections of the plurality of scrapers 4 on the plane where the disc reactor 9 is located being located on the same circle, the scraper 4 is actually installed between two adjacent monolithic discs in a spiral state.

[0124] In each scraper 4 group, the distance between the first scraper 4 and the adjacent previous monolithic disk is 30-100 mm, and the distance between the last scraper 4 and the adjacent next monolithic disk is 30-100 mm, preferably 40-80 mm, more preferably 50-70 mm. In each scraper 4 group, the axial distance between every two adjacent scrapers 4 is 15-25 mm, preferably 20-25 mm. The cross section of the scraper 4 is wedge-shaped; the thick end of the wedge faces the rotation direction of the disc reactor 9.

[0125] The plurality of spokes 8 is 5 spokes 8. Five scrapers 4 are arranged between each two adjacent monolithic discs. The number of scrapers 4 is the same as the number of spokes 8, so as to facilitate quick disassembly or cleaning.

[0126] like Figure 1As shown, the total number of disc reactors 9 in the low viscosity zone 1 is 30 to 45, the total number of disc reactors 9 in the medium-high viscosity zone 2 and the high viscosity zone 3 is 13 to 20, the total number of disc reactors 9 in the high viscosity zone 3 is 8 to 12, and the high viscosity zone is provided with 4 groups of scrapers, 8 to 12 groups. The length of the low viscosity zone 1 is half of the length of the polymerization kettle, and the total length of the medium-high viscosity zone 2 and the high viscosity zone 3 is half of the length of the polymerization kettle; the ratio of the length of the medium-high viscosity zone 2 to the high viscosity zone 3 is 1:2.

[0127] The polymerization kettle further comprises a support base 11 fixedly arranged on the inner wall of the main body and used for supporting two stirring shafts 10 .

[0128] The polymerization kettle further comprises a prepolymer inlet located at the bottom of the front end of the low viscosity zone 1 and a high viscosity melt outlet located at the bottom of the rear end of the high viscosity zone 3, and the high viscosity melt outlet is in a bell-mouth shape.

[0129] The diameter of the single disc in the high viscosity zone 3 decreases from front to back, and the diameter of the last single disc in the high viscosity zone 3 is 90% to 92% of the diameter of the first single disc. The distance between the disc reactor 9 and the top of the polymerization kettle is 200 to 300 mm. The distance between the disc reactor 9 and the bottom of the polymerization kettle is 20 to 50 mm.

[0130] The polymerization device of the present invention may also include a CHDM melt conveying system, a slurrying system, a catalyst synthesis and preparation system, a composite stabilizer preparation system, an EG recovery system, a colorant preparation system, and a melt pump post-additive injection system (for example, adding antioxidants, lubricants, anti-UV masterbatches, etc.).

[0131] Example 1

[0132] This embodiment provides a polymerization method of PETG or PCTG. The high viscosity final polymerization kettle used in the polymerization method adopts the above-mentioned structure. The specific steps of the polymerization method are as follows:

[0133] PETG polymerization:

[0134] Continuous polymerization is carried out on a 30,000 tons / year PETG continuous polymerization device, which includes a first esterification kettle, a second esterification kettle (three-chamber structure), a first prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.

[0135] First, pure terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) were added in a molar ratio of PTA:EG:CHDM = 1:0.93:0.32 (where EG is an excess feed ratio, and all CHDM enters the corresponding segments in the copolyester, and the molar percentage of the segments corresponding to CHDM in the total segments of the diol is 32%), and the total molar ratio: PTA:(EG+CHDM) = 1:1.25. The slurry was accurately measured and tetrabutyl titanate was injected into the slurry delivery pipeline as an esterification catalyst, and its total mass dosage of the melt was: 3ppm (in terms of titanium element). The prepared slurry is transported to the first esterification kettle through a screw metering pump, and the temperature in the first esterification kettle is controlled at 254-255°C, and the process tower pressure is 70-80kpa (positive pressure). The second esterification kettle is a multi-chamber design with three sub-chambers, which is convenient for adding various additives. In the second chamber of the second esterification kettle, a germanium dioxide aqueous solution is added (which is prepared by the following method: adding germanium dioxide powder to distilled water, reflux reaction, reaction for 8-10h, so that germanium dioxide reacts with water to form germanic acid. The mass concentration of germanium dioxide is 0.8%), as a polymerization catalyst (the addition of the second chamber is conducive to evaporating the catalyst Water), the amount of polymerization catalyst in the total mass of the melt is 120ppm (in terms of germanium dioxide), toner and stabilizer (phosphate, etc.) are added to the third chamber of the second esterification kettle, the second esterification kettle is a normal pressure reactor, and the esterification temperatures of the three chambers are respectively controlled as follows: 255-256°C for the first chamber, 253-254°C for the second chamber, and 257-258°C for the third chamber; the esterified materials after the esterification reaction are introduced into the first prepolymerization kettle, the first prepolymerization kettle is a vertical stirring structure, with an inner and outer chamber design, and the reaction temperature of the first prepolymerization kettle is controlled at 258-260°C, and the vacuum degree is 9.0Kpa, and the oligomers polymerized in the first prepolymerization kettle are introduced into the second prepolymerization kettle. The first prepolymerization kettle is a uniaxial horizontal disc reactor. The reaction temperature of the second prepolymerization kettle is controlled at 260-262°C. The prepolymer after the reaction in the second prepolymerization kettle is introduced into the high viscosity final polymerization kettle through a prepolymer melt pump and a prepolymer filter. The high viscosity final polymerization reactor adopts the aforementioned specific structure to control its reactor outlet temperature at 265-268°C, vacuum degree at 80-110 Pa, outlet melt dynamic viscosity at 635-650 Pa.s, and outlet PETG characteristic viscosity at 0.781 (measured in a mixed solvent with a volume ratio of phenol: tetrachloroethane of 3:2). The PETG slice indicators are shown in Table 1.

[0136] Or PCTG polymerization:

[0137] Continuous polymerization is carried out on a 30,000 t / a PCTG continuous polymerization unit, which includes a first esterification kettle, a second esterification kettle (three-chamber structure), a first prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.

[0138] First, pure terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) were accurately measured for slurry preparation, and tetrabutyl titanate was injected into the slurry delivery pipeline as an esterification catalyst, and its total mass dosage of the melt was 3ppm (in terms of titanium). element), the prepared slurry is transported to the first esterification kettle through a screw metering pump, the temperature in the first esterification kettle is controlled at 256-257°C, the process tower pressure is 70-80kpa (positive pressure), the second esterification kettle is a multi-chamber design with three sub-chambers, which is convenient for adding various additives, and a germanium dioxide aqueous solution (its preparation method is the same as above. The mass concentration of germanium dioxide is 0.8%) is added to the second chamber of the second esterification kettle as a polymerization catalyst (the addition of the second chamber is conducive to evaporating the water in the catalyst), and the polymerization catalyst accounts for 120ppm (in terms of germanium dioxide) of the total mass of the melt. The toner and stabilizer (phosphate, etc.) are added to the three esterification chambers. The second esterification kettle is a normal pressure reactor. The esterification temperatures of the three chambers are controlled as follows: 255-256°C for the first chamber, 253-254°C for the second chamber, and 260-262°C for the third chamber. The esterified materials after the esterification reaction are introduced into the first prepolymerization kettle. The first prepolymerization kettle is a vertical stirring structure with an inner and outer chamber design. The reaction temperature of the first prepolymerization kettle is controlled at 266-268°C and the vacuum degree is 9.0Kpa. The oligomers polymerized in the first prepolymerization kettle are introduced into the second prepolymerization kettle. The second prepolymerization kettle is a single-axis horizontal disc reactor. The reaction temperature of the second prepolymerization kettle is 272-274°C. The prepolymer after the reaction in the second prepolymerization kettle is introduced into the high-viscosity final polymerization kettle through the prepolymer melt pump and the prepolymer filter. The high-viscosity final polymerization reactor is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 280-282°C, the vacuum degree is 90-110 Pa, the outlet melt dynamic viscosity is controlled at 600-620 Pa.s, and the outlet PCTG intrinsic viscosity is controlled at 0.801 (measured in a mixed solvent with a volume ratio of phenol: tetrachloroethane of 3:2). The PCTG slice indicators are shown in Table 2.

[0139] Example 2

[0140] This embodiment provides a polymerization method for PETG or PCTG. The high-viscosity final polymerization kettle used in the polymerization method adopts the above-mentioned structure. The specific steps of the polymerization method are basically the same as those in Example 1, except that the polymerization catalyst is first vacuum distilled from a germanium dioxide aqueous solution, and after half of the total mass of water is distilled out, an equal mass of fresh ethylene glycol EG is added under stirring conditions to prepare a solution in which germanium dioxide is dispersed in a mixed solvent of water and ethylene glycol, the mass concentration of germanium dioxide is also 0.8%, and the mass ratio of water to ethylene glycol is 1:1. The polymerization results are shown in Table 1-2 below.

[0141] Example 3

[0142] This embodiment provides a polymerization method for PETG or PCTG. The high-viscosity final polymerization kettle used in the polymerization method adopts the above-mentioned structure. The specific steps of the polymerization method are basically the same as those in Example 1, except that the polymerization catalyst is replaced by a surface-deposited supported germanium-based catalyst (the carrier is nanoporous barium sulfate) from a germanium dioxide aqueous solution.

[0143] The preparation method of the catalyst is as follows:

[0144] 1) Ethylene glycol is heated to 50° C., and accurately measured barium hydroxide octahydrate is slowly added into the reactor under high-speed stirring conditions (high-speed homogenizer: speed: 3000-6000 rpm), stirred until completely dissolved, and then 10% mass concentration of dilute sulfuric acid is quickly added into the reactor according to the molar ratio of barium ions, and kept stirring at high speed for 1.0 hour. The reaction heat causes the suspension to be heated to about 90° C., and the pH of the suspension is adjusted to be stable at 7.0, and then the temperature is raised to reflux, and the water is evaporated, and the temperature is lowered to 170° C., and ethylene glycol is added to make the mass content of barium sulfate powder 20%, and then stirred for 0.5 hour, and the pH value is measured again until the pH value of the suspension is completely stable at 7.0. The particle size of the obtained barium sulfate powder is 20 nm, and the specific surface area is 350 m 2 / g.

[0145] 2) Tetraethyl silicate and sodium hydroxide are added dropwise to the ethylene glycol suspension of barium sulfate with a pH value of 7.0, so that the surface of the barium sulfate powder is coated with a silicon dioxide layer; after aging for 6 hours, the prepared mixed aqueous solution of calcium chloride, aluminum chloride, and zirconium acetate (wherein the molar concentration of calcium chloride is 2.5 mol / L, the molar concentration of aluminum chloride is 0.5 mol / L, and the molar concentration of zirconium acetate is 0.8 mol / L) and the mixed aqueous solution of sodium hydroxide and sodium bicarbonate with a total molar concentration of 0.5 mol / L are added dropwise to the reactor at the same time under high-speed stirring conditions, according to the total valence of the above three metal ions being equal to the total valence of hydroxide and carbonate ions, and the pH value of the suspension is strictly controlled to be between 10.0 and 10.2 during the dropping process. The dropping time is controlled to be 11 hours, and the reaction temperature is controlled to be 80°C, so that the above three metals are deposited on the surface of the carrier. The obtained suspension was stirred and aged for 1.0 hour, and then stirred under pressure (pressure of 0.7Mpa), and heated to 180°C at the same time. After balancing for 2.0 hours, the pressure was quickly released to normal pressure, and the suspension was cooled to room temperature, filtered, washed, dried, and crushed by an ultrafine grinder, and then placed in a muffle furnace for calcination at 290°C for 6 hours. The metal basic carbonate deposited on the surface of the carrier was dehydrated and made porous, so that a load deposition layer with a porous structure was formed on the surface of the carrier. The specific surface area of ​​the carrier containing the load deposition layer is 600 to 900 m 2 / g.

[0146] 3) Add distilled water to the carrier containing the load deposition layer obtained in step 2) under stirring conditions to prepare a suspension with a mass percentage of 20%. After grinding the suspension twice with an ultrafine grinder, the suspension is heated to 90°C. A certain amount of germanium tetrachloride is slowly added to the above suspension under stirring conditions within 4.0 hours. Germanium tetrachloride and water undergo hydrolysis reaction to generate germanium dioxide, which is deposited on the surface of the load deposition layer. During the dropwise addition, sodium hydroxide is used to adjust the pH of the suspension so that the pH is maintained between 10.0 and 10.2. After the dropwise addition is completed, continue to stir and age at 90°C for 1.5 hours, then slowly add a certain amount of silicate to the suspension within 2.0 hours. After the dropwise addition is completed, continue to age for 1.0 hour to obtain a suspension of the catalyst. The mass ratio of silicate to germanium tetrachloride is 1:0.2.

[0147] 4) The catalyst suspension is filtered, washed with distilled water, dried and crushed to obtain a supported germanium-based catalyst powder, which can be directly packaged and stored. When used for polymerization, the powder is dispersed in ethylene glycol to obtain a suspension, in which the mass percentage of the catalyst powder is 20%. The specific surface area of ​​the catalyst powder is 280 m 2 / g, and the particle size is 100nm. In the catalyst powder, the mass ratio of effective germanium in the carrier, the load deposition layer and the active component is 72.5:7.5:5.0.

[0148] The aggregation results are shown in Table 1-2 below.

[0149] Example 4

[0150] This embodiment provides a polymerization method for PETG or PCTG. The high-viscosity final polymerization kettle used in the polymerization method adopts the above-mentioned structure. The specific steps of the polymerization method are basically the same as those in Example 3, except that: the polymerization catalyst carrier is different. Specifically, when preparing the polymerization catalyst, step 1) is not performed, and the ethylene glycol suspension of barium sulfate with a pH value of 7.0 in step 2) is replaced by a water suspension of γ-nanoporous alumina with a pH value of 7.0, wherein the particle size of the γ-nanoporous alumina is 35 nm and the specific surface area is 240 m 2 / g.

[0151] The aggregation results are shown in Table 1-2 below.

[0152] Example 5

[0153] This embodiment provides a polymerization method for PETG or PCTG. The high-viscosity final polymerization kettle used in the polymerization method adopts the above-mentioned structure. The specific steps of the polymerization method are basically the same as those in Example 3, except that: the polymerization catalyst carrier is different. Specifically, when preparing the polymerization catalyst, step 1) is not performed, and the ethylene glycol suspension of barium sulfate with a pH value of 7.0 in step 2) is replaced by a water suspension of nanoporous alumina-zirconia powder with a pH value of 7.0, wherein the particle size of the nanoporous alumina-zirconia powder is 60nm and the specific surface area is 300m 2 / g.

[0154] The aggregation results are shown in Table 1-2 below.

[0155] Example 6

[0156] This embodiment provides a polymerization method for PETG or PCTG. The high-viscosity final polymerization kettle used in the polymerization method adopts the aforementioned structure. The specific steps of the polymerization method are basically the same as those in Example 1, with the only difference being that the polymerization catalyst is replaced by a surface-deposited supported germanium-based catalyst (the carrier is nanoporous barium sulfate) with a surface-deposited supported titanium-germanium-based composite catalyst (the carrier is nanoporous barium sulfate).

[0157] The preparation method of the catalyst is basically the same as that of Example 3, except that a titanium source and a germanium source are added simultaneously in step 3) when preparing the catalyst. Step 3) is as follows: distilled water is added to the carrier containing the load deposition layer obtained in step 2) under stirring conditions to prepare a suspension with a mass percentage of 20%. After grinding the suspension twice with an ultrafine grinder, the suspension is heated to 90° C. A certain amount of dilute hydrochloric acid solution of germanium tetrachloride and a certain amount of tetrabutyl titanate are slowly added dropwise to the above suspension under stirring conditions within 4.0 hours. Germanium tetrachloride reacts with water to generate germanium dioxide, and tetrabutyl titanate reacts with water to generate titanium dioxide. Both are deposited on the surface of the load deposition layer. During the addition process, sodium hydroxide is used to adjust the pH of the suspension so that the pH is maintained between 10.0 and 10.2. After the addition is completed, the suspension is stirred and aged for 1.5 hours at 90°C, and then a certain amount of silicate is slowly added to the suspension within 2.0 hours. After the addition is completed, the suspension is aged for 1.0 hours to obtain a catalyst suspension. The ratio of the mass of silicate to the total mass of germanium tetrachloride and tetrabutyl titanate is 1:0.2. The molar ratio of tetrabutyl titanate to germanium tetrachloride is 1:1.5.

[0158] The specific surface area of ​​the catalyst powder obtained in step 4) is 280 m 2 / g, and the particle size is 100nm. In the catalyst powder, the mass ratio of the carrier, the load deposition layer, the effective germanium in the active component, and the effective titanium in the active component is 78.1:7.5:2.5:1.25. The EG catalyst suspension obtained in step 4) is a stable suspension and can be stored for 5 months without sedimentation.

[0159] The aggregation results are shown in Table 1-2 below.

[0160] Example 7

[0161] This embodiment provides a polymerization method for PETG or PCTG. The high-viscosity final polymerization kettle used in the polymerization method adopts the above-mentioned structure. The specific steps of the polymerization method are basically the same as those in Example 6, except that the polymerization catalyst is replaced by a surface-deposited supported titanium-germanium-based composite catalyst (the carrier is nanoporous barium sulfate) with a surface-deposited supported titanium-germanium-based composite catalyst (the carrier is γ-nanoporous alumina powder). When preparing the catalyst, step 1) is not performed, and the ethylene glycol suspension of barium sulfate with a pH value of 7.0 in step 2) is replaced with a water suspension of γ-nanoporous alumina with a pH value of 7.0, wherein the particle size of the γ-nanoporous alumina is 35nm and the specific surface area is 240m 2 / g.

[0162] The aggregation results are shown in Table 1-2 below.

[0163] Example 8

[0164] This embodiment provides a polymerization method for PETG or PCTG. The high-viscosity final polymerization kettle used in the polymerization method adopts the above-mentioned structure. The specific steps of the polymerization method are basically the same as those in Example 6, except that the polymerization catalyst is replaced by a surface-deposited supported titanium-germanium-based composite catalyst (the carrier is nanoporous barium sulfate) with a surface-deposited supported titanium-germanium-based composite catalyst (the carrier is nanoporous alumina-zirconia powder). When preparing the catalyst, step 1) is not performed, and the ethylene glycol suspension of barium sulfate with a pH value of 7.0 in step 2) is replaced with a water suspension of nanoporous alumina-zirconia powder with a pH value of 7.0, wherein the particle size of the nanoporous alumina-zirconia powder is 60nm and the specific surface area is 300m 2 / g.

[0165] The aggregation results are shown in Table 1-2 below.

[0166] Comparative Example 1

[0167] This comparative example provides a polymerization method for PETG or PCTG. The high-viscosity final polymerization kettle used in the polymerization method is a common horizontal front-to-back biaxial polymerization kettle. The front-to-back biaxial arrangement and the disc reactor arrangement in the polymerization kettle are the same as those of the polymerization kettle of the present invention, and a scraper is also arranged between each adjacent two disc reactors in the high-viscosity zone, but the scraper is an integral arrangement of the polymerization kettle wall, and multiple split scrapers are not arranged. The specific steps of the polymerization method of comparative example 1 are the same as those of embodiment 1. The polymerization results are shown in the following tables 1-2.

[0168] The polyester melt obtained in each embodiment and comparative example was sliced, and various properties of the slices were tested using the GB / T 14190-2017 standard. The results are shown in Tables 1-2 below, where IV refers to the intrinsic viscosity, which is measured in a mixed solvent of phenol and tetrachloroethane in a volume ratio of 3:2, and DEG, H2O, ash, Fe, and agglomerated particles refer to the mass fraction contents of diethylene glycol, water, ash, Fe element, and agglomerated particles in the polyester, respectively.

[0169] Table 1 PETG physical and chemical indicators

[0170]

[0171]

[0172] Table 2 Physical and chemical indicators of PCTG

[0173]

[0174] It can be seen that by using the specific high-viscosity polymerization kettle of the present invention, a PETG or PCTG melt with high viscosity can be prepared. And under the condition of ensuring other excellent properties, the color performance of the polymerization product can be significantly improved. At the same time, the polymerization kettle can extend the operation cycle of the polymerization device and is easy to clean.

[0175] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A polymerization kettle for preparing a PETG or PCTG melt, wherein the intrinsic viscosity of the PETG or PCTG melt is above 0.770, characterized in that: The polymerization kettle is a horizontal polymerization kettle, and includes a main body with a chamber inside, the main body includes a low viscosity zone, a medium-high viscosity zone, and a high viscosity zone arranged in sequence along the axial direction of the polymerization kettle, and the viscosity of the PETG or PCTG melt in the low viscosity zone, the medium-high viscosity zone, and the high viscosity zone increases in sequence; the polymerization kettle also includes two stirring shafts, one of which is arranged in the low viscosity zone, and the other is arranged in the high viscosity zone and the medium-high viscosity zone; a plurality of disc reactors are arranged on the two stirring shafts, the disc reactor in the low viscosity zone is 6 to 8 groups of combined discs, each group is 3-10 discs; the disc reactor in the medium-high viscosity zone is 5 to 8 groups of double-disc or triple-disc combined discs; the disc reactor in the high viscosity zone is a single disc, and the single disc is detachably arranged in the polymerization kettle; a scraper group is also arranged on the wall of the polymerization kettle between each two adjacent single discs in the high viscosity zone, the scraper group includes a plurality of scrapers, and the distance between each scraper and the adjacent single disc is different.

2. The polymerizer for preparing a PETG or PCTG melt according to claim 1, wherein: The disc reactor in the high viscosity zone comprises a ring and a plurality of spokes arranged inside the ring, the ring comprises a first part and a second part, the first part is fixedly connected to the plurality of spokes respectively, and the second part is detachably connected to the first part.

3. The polymerizer for preparing a PETG or PCTG melt according to claim 2, wherein: The detachable connection is a threaded connection; and / or, the plurality of spokes is 5 spokes.

4. The polymerizer for preparing a PETG or PCTG melt according to claim 2, wherein: Positioning screw holes are designed to extend left and right from the spoke top of the disc reactor in the high viscosity area, and the circular rings of adjacent spokes are designed with detachable segmented circular rings, which cooperate with the positioning screw holes at the spoke ends and are butt-jointed with impact bolts to form a smooth entire circular ring.

5. The polymerizer for preparing a PETG or PCTG melt according to claim 1, wherein: The multiple scrapers are arranged vertically, the ends of the scrapers point to the axis of the stirring shaft, and the projections of the multiple scrapers on the plane where the disc reactor is located are located on the same circle.

6. The polymerizer for preparing a PETG or PCTG melt according to claim 5, characterized in that: The length of each scraper is the same; and / or, between each two adjacent single discs in the high viscosity area, the distance between the scraper and the adjacent previous single disc is distributed in an arithmetic progression; and / or, in each scraper group, the axial distance between each two adjacent scrapers is 15 to 25 mm.

7. The polymerizer for preparing a PETG or PCTG melt according to claim 6, characterized in that: In each scraper group, the distance between the first scraper and the adjacent previous single-piece disk is 30-100 mm, and the distance between the last scraper and the adjacent next single-piece disk is 30-100 mm.

8. The polymerizer for preparing a PETG or PCTG melt according to claim 1, wherein: The cross section of the scraper is wedge-shaped; the thick end of the wedge faces the rotation direction of the disc reactor; and / or, five scrapers are arranged between every two adjacent single discs.

9. The polymerizer for preparing a PETG or PCTG melt according to claim 1, wherein: The total number of disc reactors in the low viscosity zone is 30 to 45, the total number of disc reactors in the medium-high viscosity zone and the high viscosity zone is 13 to 20, the total number of disc reactors in the high viscosity zone is 8 to 12, and 8 to 12 scraper groups are arranged in the high viscosity zone.

10. The polymerization reactor for preparing a PETG or PCTG melt according to claim 1, characterized in that: The length of the low viscosity zone is half of the length of the polymerization kettle, and the total length of the medium-high viscosity zone and the high viscosity zone is half of the length of the polymerization kettle; the length ratio of the medium-high viscosity zone to the high viscosity zone is 1:

2.

11. The polymerizer for preparing a PETG or PCTG melt according to claim 1, characterized in that: The polymerization kettle also includes a support base fixedly arranged on the inner wall of the main body for supporting two stirring shafts; and / or, the polymerization kettle also includes a prepolymer inlet located at the bottom of the front end of the low viscosity zone and a high viscosity melt outlet located at the bottom of the rear end of the high viscosity zone, and the high viscosity melt outlet is in a bell-mouth shape.

12. The polymerizer for preparing a PETG or PCTG melt according to claim 1, characterized in that: The diameter of the single disk in the high viscosity zone decreases from front to back, and the diameter of the last single disk in the high viscosity zone is 90% to 92% of the diameter of the first single disk; and / or, the distance between the disc reactor and the top of the polymerization kettle is 200 to 300 mm; and / or, the distance between the disc reactor and the bottom of the polymerization kettle is 20 to 50 mm.

13. A method for polymerizing PETG or PCTG, wherein the intrinsic viscosity of the PETG or PCTG is greater than 0.770, characterized in that: The polymerization method comprises the steps of subjecting terephthalic acid, ethylene glycol and 1,4-cyclohexanedimethanol to an esterification reaction in a first esterification kettle and a second esterification kettle, a prepolymerization reaction in a first prepolymerization kettle and a second prepolymerization kettle to obtain a prepolymer, and a step of subjecting the prepolymer to a polymerization reaction in a final polymerization kettle to obtain the PETG or PCTG. The final polymerization kettle is the polymerization kettle for preparing a PETG or PCTG melt according to any one of claims 1 to 12.

14. The polymerization method of PETG or PCTG according to claim 13, characterized in that: The intrinsic viscosity of the PETG is 0.770-0.820, and the intrinsic viscosity of the PCTG is 0.790-0.

820.

15. The polymerization method of PETG or PCTG according to claim 13, characterized in that: The polymerization method further comprises the step of adding an esterification catalyst into the first esterification kettle before the esterification reaction, wherein the esterification catalyst is selected from tetrabutyl titanate, tetraisopropyl titanate or tetra(2-ethylhexyloxy) titanate.

16. The polymerization method of PETG or PCTG according to claim 15, characterized in that: The mass of the titanium element in the esterification catalyst accounts for 1 to 3 ppm of the mass of the PETG or PCTG.

17. The polymerization method of PETG or PCTG according to claim 13, characterized in that: The esterification reaction in the first esterification kettle is carried out at a pressure of 70 to 80 kPa; and / or, the esterification reaction in the first esterification kettle is carried out at 255 to 257° C.; and / or, the prepolymerization reaction in the first prepolymerization kettle is carried out at a vacuum degree of 9 to 12 kPa; and / or, the prepolymerization reaction in the first prepolymerization kettle is carried out at a vacuum degree of 9 to 12 kPa; and / or, the prepolymerization reaction in the first prepolymerization kettle is carried out at a vacuum degree of 9 to 12 kPa; and / or, the prepolymerization reaction in the first prepolymerization kettle is carried out at 258 to 266° C.; and / or, the prepolymerization reaction in the second prepolymerization kettle is carried out at a vacuum degree of 0.9 to 1.3 kPa; and / or, the prepolymerization reaction in the second prepolymerization kettle is carried out at 260 to 267° C.; and / or, the polymerization reaction in the final polymerization kettle is carried out at a vacuum degree of 100 to 130 Pa; and / or, the polymerization reaction in the final polymerization kettle is carried out at 265 to 275° C.

18. The polymerization method of PETG or PCTG according to claim 13, characterized in that: The esterification reaction in the second esterification kettle is carried out under normal pressure; and / or, the second esterification kettle is a horizontal reactor and comprises three chambers arranged in sequence front to back, and the polymerization method further comprises the step of injecting a polymerization catalyst into the third chamber from the front to the back of the second esterification kettle.

19. The polymerization method of PETG or PCTG according to claim 18, characterized in that: The polymerization catalyst is selected from a germanium dioxide aqueous solution, a suspension of germanium dioxide dispersed in a mixed solvent of water and ethylene glycol, a surface-deposited supported germanium-based catalyst, and a surface-deposited supported titanium-germanium-based composite catalyst; The surface-deposited supported germanium-based catalyst and the surface-deposited supported titanium-germanium-based composite catalyst include a carrier, a supported deposited layer and an active component. The carrier is an inorganic porous material coated and modified by silicate. The supported deposited layer is located on the carrier and has a porous structure. The active component is deposited on the supported deposited layer. The surface-deposited supported germanium-based catalyst is prepared by a preparation method comprising the following steps: subjecting a suspension of a carrier, a water-soluble calcium salt, a water-soluble aluminum salt, a water-soluble zirconium salt, a water-soluble hydroxide and a base to precipitation reaction, filtering and calcining to form the supported deposited layer on the carrier; the base is selected from carbonate and / or bicarbonate; the specific surface area of ​​the carrier containing the supported deposited layer is greater than the specific surface area of ​​the carrier; the carrier containing the supported deposited layer is dispersed in water to obtain a suspension of the carrier containing the supported deposited layer; The suspension of the carrier containing the supported deposition layer is subjected to a hydrolysis reaction with a germanium source to obtain a catalyst precursor; the catalyst precursor is subjected to a coating reaction with a silicate and water to load an active component on the supported deposition layer to obtain a surface-deposited supported germanium-based catalyst; The surface-deposited supported titanium-germanium-based catalyst is prepared by a preparation method comprising the following steps: subjecting a suspension of a carrier, a water-soluble calcium salt, a water-soluble aluminum salt, a water-soluble zirconium salt, a water-soluble hydroxide and a base to precipitation reaction, filtering and calcining to form the supported deposition layer on the carrier; the base is selected from carbonate and / or bicarbonate; the specific surface area of ​​the carrier containing the supported deposition layer is greater than the specific surface area of ​​the carrier; the carrier containing the supported deposition layer is dispersed in water to obtain a suspension of the carrier containing the supported deposition layer; The suspension of the carrier containing the loaded deposition layer is subjected to a hydrolysis reaction with a hydrochloric acid solution of a germanium source and a titanium source to obtain a catalyst precursor; the catalyst precursor is subjected to a coating reaction with a silicate and water, and an active component is loaded on the loaded deposition layer to obtain a surface-deposited loaded titanium-germanium-based composite catalyst.

20. The polymerization method of PETG or PCTG according to claim 19, characterized in that: The polymerization catalyst is selected from a germanium dioxide aqueous solution or a suspension of germanium dioxide dispersed in a mixed solvent of water and ethylene glycol, the mass of germanium dioxide in the polymerization catalyst accounts for 100-150 ppm of the mass of PETG or PCTG; or, the polymerization catalyst is selected from a surface-deposited supported germanium-based catalyst, the mass of the germanium element in the polymerization catalyst accounts for 50-75 ppm of the mass of PETG or PCTG, calculated as germanium dioxide; or, the polymerization catalyst is selected from a surface-deposited supported titanium-germanium-based composite catalyst, the mass of the titanium element and the germanium element in the polymerization catalyst account for 8-12 ppm and 25-50 ppm of the mass of PETG or PCTG, calculated as germanium dioxide.

21. The polymerization method of PETG or PCTG according to claim 13, characterized in that: The polymerization method further includes the step of pre-melting 1,4-cyclohexanedimethanol and conveying the molten 1,4-cyclohexanedimethanol to the first esterification kettle.

22. The polymerization method of PETG or PCTG according to claim 13, characterized in that: The polymerization kettle also includes steam feed ports for introducing superheated ethylene glycol steam, which are arranged at the top of the main body at the rear end of the low viscosity zone, the rear end of the medium and high viscosity zone, and the rear end of the high viscosity zone. The polymerization method also includes the step of using a metering system to meter the superheated ethylene glycol steam and introducing it into the final polymerization kettle.

23. The polymerization method of PETG or PCTG according to claim 13, characterized in that: When preparing PETG, the feeding molar ratio of the terephthalic acid, ethylene glycol, and 1,4-cyclohexanedimethanol is 1: 0.92-0.93: 0.325-0.315; or, when preparing PCTG, the feeding ratio of the terephthalic acid, ethylene glycol, and 1,4-cyclohexanedimethanol is 1: 0.63-0.64: ​​0.610-0.

615.

24. PETG or PCTG prepared by the polymerization method of PETG or PCTG according to any one of claims 13 to 23.

Citation Information

Patent Citations

  • Polymerization kettle for high-viscosity PETG or PCTG and polymerization method of PETG or PCTG

    CN118765213A